Nonverts : the making of ex-Christian America - Bullivant, Stephen Sebastian, 1984- (Oxford University Press, 2022)
"The United States is in the midst of a religious revolution. Or, perhaps it is better to say a non-religious revolution. Around a quarter of US adults now say they have no religion. The great majority of these religious "nones" also say that they used to belong to a religion but no longer do. These are the nonverts: think "converts," but from having religion to having none. Even on the most conservative of estimates, there are currently about 59 million of them in the United States. Nonverts explores who they are, and why they joined the rising tide of the ex-religious. It draws on dozens of interviews, original analysis of high-quality survey data, and a wealth of cutting-edge studies, to present an entertaining and insightful exploration of America's ex-religious landscape. While American religion is not going to die out any time soon, ex-Christian America is a growing presence in national life. America's religious revolution is not just a religious revolution : it is catalyzing a profound social, cultural, moral, and political impact"--